2017
DOI: 10.1016/j.adolescence.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of parental monitoring and socioeconomic status in predicting minor delinquency between and within adolescents

Abstract: This six-wave multi-informant longitudinal study on Dutch adolescents (N = 824; age 12-18) examined the interplay of socioeconomic status with parental monitoring in predicting minor delinquency. Fixed-effects negative binomial regression analyses revealed that this interplay is different within adolescents across time than between adolescents. Between individuals, parental solicitation and control were not significantly associated with delinquency after controlling for SES: Adolescents whose parents exercised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 77 publications
2
38
0
1
Order By: Relevance
“…However, in contrast to key parenting theories (Patterson 1982;Stattin and Kerr 2000), there was also a substantial amount of studies that did not consistently show such linkages. Two studies even found the opposite of what one would expect: adolescents reported more externalizing problems at times or before they had perceived more parental control (Coley et al 2009;Rekker et al 2017). Furthermore, the within-family studies on parental control and adolescent disclosure showed significant concurrent associations in the expected direction but found no evidence of time-lagged effects Villalobos Solís et al 2015).…”
Section: Parenting Processes On Adaptation Dimensions: What Do We Knomentioning
confidence: 95%
See 4 more Smart Citations
“…However, in contrast to key parenting theories (Patterson 1982;Stattin and Kerr 2000), there was also a substantial amount of studies that did not consistently show such linkages. Two studies even found the opposite of what one would expect: adolescents reported more externalizing problems at times or before they had perceived more parental control (Coley et al 2009;Rekker et al 2017). Furthermore, the within-family studies on parental control and adolescent disclosure showed significant concurrent associations in the expected direction but found no evidence of time-lagged effects Villalobos Solís et al 2015).…”
Section: Parenting Processes On Adaptation Dimensions: What Do We Knomentioning
confidence: 95%
“…However, studies have also found the opposite pattern. For example, parental control was higher in low-SES families (but not high-SES families) when adolescent delinquency was higher (Rekker et al 2017). Additionally, an increase in adolescent risky sexual behavior predicted a subsequent increase in paternal knowledge (Coley et al 2009).…”
Section: Parental Controlmentioning
confidence: 99%
See 3 more Smart Citations